Fully constrained acetabular liner vs. dual mobility hip joint in the surgical treatment of metastatic bone disease of the hip: study protocol for a randomized, open-label, two-arm, non-inferiority trial evaluating the post-operative hip dislocation rate - Afrim Iljazi; Michala Skovlund Sørensen; Kolja Sebastian Weber; Allan Villadsen; Frank Eriksson; Michael Mørk Petersen (Trials, 2023)
Abstract Background Patients receiving total hip arthroplasty (THA) due to metastatic bone disease of the hip (MBD) are at an increased risk of post-operative joint dislocation compared to other populations. Different joint solutions have been developed with the purpose of reducing the dislocation risk compared to regular THAs. One of these solutions, the constrained liner (CL), has been used increasingly at our department in recent years. This design, however, is prone to polyethylene wear and higher revision rates. An alternative is the dual mobility cup (DM), which has been shown to reduce the risk of dislocation in other high-risk populations. Few studies have investigated DM for THA due to MBD, and no studies have directly compared these two treatments in this population. We therefore decided to conduct a trial to investigate whether DM is non-inferior to CL regarding the post-operative joint dislocation risk in patients receiving THA due to MBD. Materials and methods This study is a single-center, randomized, open-label, two-arm, non-inferiority trial. We will include 146 patients with MBD of the hip who are planned for THA at the Department of Orthopedic Surgery, Rigshospitalet. Patients with previous osteosynthesis or endoprosthetic surgery of the afflicted hip, or who are planned to receive partial pelvic reconstruction or total femoral replacement, will be excluded. Patients will be stratified by whether subtrochanteric bone resection will be performed and allocated to either CL or DM in a 1:1 ratio. The primary outcome is the 6 months post-operative joint dislocation rate. Secondary outcomes include overall survival, implant survival, the rate of other surgical- and post-operative complications, and quality of life and functional outcome scores. Discussion This study is designed to investigate whether DM is non-inferior to CL regarding the risk of post-operative dislocation in patients receiving THA due to MBD. To our knowledge, this trial is the first of its kind. Knowledge gained from this trial will help guide surgeons in choosing a joint solution that minimizes the risk of dislocation and, ultimately, reduces the need for repeat surgeries in this patient population. Trial registration ClinicalTrials.gov Identifier: NCT05461313. Registered on July 15 2022. This trial is reported according to the items in the WHO Trial Registration Data Set (Version 1.3.1).